2013
DOI: 10.1016/j.cyto.2012.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor (MIF): Genetic evidence for participation in early onset and early stage rheumatoid arthritis

Abstract: Macrophage migration inhibitory factor (MIF) is an upstream pro-inflammatory cytokine that is associated with the pathogenesis of autoimmune inflammatory diseases including rheumatoid arthritis (RA).Two polymorphisms in the upstream region exist in the MIF gene and are associated with RA susceptibility or severity in different populations. In this case-control study, we investigated whether MIF polymorphisms are associated with RA susceptibility or activity in a western Mexican population .The relationship of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
58
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 49 publications
(77 reference statements)
15
58
3
1
Order By: Relevance
“…Regarding the genotype and allele frequencies, both polymorphisms were distributed similarly to those reported in our previous study of a Mexican-Mestizo population by Llamas-Covarrubias et al [22] Unlike this previous study, in the case of the −794 CATT 5-8 MIF polymorphism we did not observe the presence of genotypes with the −794 CATT 8 high expression allele which was reported in low frequency (1%) in Mexican Mestizo patients with rheumatoid arthritis (RA). When we compared genotype and allele frequencies of both polymorphisms with frequencies reported in European Caucasians populations in the Netherlands [18], a Spanish population, [27] Caucasian Americans and African Americans populations [28] we observed that the genotype frequencies in our population were distributed similarly to those reported in these previous studies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the genotype and allele frequencies, both polymorphisms were distributed similarly to those reported in our previous study of a Mexican-Mestizo population by Llamas-Covarrubias et al [22] Unlike this previous study, in the case of the −794 CATT 5-8 MIF polymorphism we did not observe the presence of genotypes with the −794 CATT 8 high expression allele which was reported in low frequency (1%) in Mexican Mestizo patients with rheumatoid arthritis (RA). When we compared genotype and allele frequencies of both polymorphisms with frequencies reported in European Caucasians populations in the Netherlands [18], a Spanish population, [27] Caucasian Americans and African Americans populations [28] we observed that the genotype frequencies in our population were distributed similarly to those reported in these previous studies.…”
Section: Discussionsupporting
confidence: 85%
“…In our previous study by Llamas-Covarrubias et al, the association of the −794 CATT 7 and −173*C high expression alleles with early onset of RA and disease activity was reported in a Mexican-Mestizo population, where both high expression alleles presented a strong linkage disequilibrium (LD = 0.87, p <0.001) which indicates that both alleles are segregated in block from one generation to another and may confer a similar risk [22]. In a Spanish population with SLE, Sánchez et al also reported the association of −794 CATT 7 and −173*C high expression alleles with increased susceptibility to present SLE (OR = 2, p <0.01) [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering TNFa serum levels were overexpressed and MIF values were normal as previously reported (2-6 ng/mL) 38 these results could provide further insight into TNFa's association with disease activity and MIF with disease progression 39 .…”
Section: Discussionmentioning
confidence: 61%
“…They have not found a significant association between G/G, G/C and C/C genotype distributions whereas they have shown that the risk of RA disease is high in individuals who carry C/C genotype. In another study related to RA patients, it has been stated that C allele is related to the activity of RA disease (16). It was have determined that the MIF -173 C is related to inflammatory sensitivity of polyarthritis whereas it is not in association with the intensity of the disease (17).…”
Section: Discussionmentioning
confidence: 99%